The Impact of Motivation on Foreign Language Learning: A Longitudinal Study - Sherly Franchisca; Mike Nurmalia Sari; Nurfitri Nurfitri; Merlyn Kristine Nelloe; Aria Mulyapradana; Nining Fitriani (Departement of Mathematics Education, 2024)
This article synthesizes insights from a series of longitudinal studies investigating the impact of motivation on foreign language learning. The studies, spanning various contexts and methodologies, collectively reveal a dynamic and fluctuating nature of motivation. Learners' motivation evolves not only over the course of language programs but also within individual classes, influenced by external factors such as the learning environment and the presence of anxiety. The role of educators in shaping positive language learning experiences, strategies to counteract decreasing motivation, and the positive outcomes of integrating content and language learning are discussed. The findings underscore the need for a holistic and adaptive approach to language education that recognizes the multifaceted nature of motivation.